CONTENT OF GENERAL LIPIDS AND THEIR SEPARATE CLASSES AFTER ADDITIONAL FERTILIZING BY CITRATES OF Ag AND Cu IN THE TISSUES OF HONEY BEES AND PRODUCTS - Двилюк, І. І.; Ковальчук, І. І.; Романів, Л. І. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
It is Presented data on the content of total lipids and value their classes in the body of honey bees and their products under feeding sugar syrup with the addition nan ocitrates Ag and Cu. Results of the studies were observed which increased in the total lipids in the tissues of the honey bees’ whole body of bee-bread and honeycombs. Results showed difference in value of certain classes of lipids in bee tissues tested groups, including phospholipids higher levels, mono - and diacylglycerols, against reducing the number of free cholesterol. In bee-bread and honey combs tested groups noted higher levels of phospholipids in the background of lower nonetherified fatty acids. The changes of total lipids and their factions in the body of bees feeding conditions for different amounts of syrup citrate Ag and Cu indicate adose-dependent stimulating effect of these compounds on lipid metabolism and their separate fractions in the honeybee’s tissues.